Informal Caregivers of Palliative Oncohematologic Patients: The Invisible Guests: An Exhaustive Review of the Literature Available. (August 2016) - Uceda-Torres, María Elena; Rodríguez-Rodríguez, Juan Nicolás; Alvarado-Gómez, Francisco; Sánchez-Ramos, José Luis; McGrath, Pam
Informal caregivers are crucial members of the teams that care for palliative patients with cancer, including those with oncohematological malignancies. Publications concerning specific aspects of this latter group of carers are limited. This literature review indicates that palliative oncohematologic patients' caregivers do not differ from those of patients with solid tumors in ethical and related problems. However, there are specific problems for the former group with regard to negotiating the curative system, which are experienced as distressing, often without support from the health system and without offers of the possibility of being referred to palliative teams that they would have valued as very positive. Although this tendency seems to be changing, there is still considerable work to be done to improve the role of these carers.